Resale Price Maintenance and the Service Argument (in the Book Trade) - Norbert Schulz (University of Würzburg, Department of Economics, 2004)
The paper introduces a specification of the demand side which allows RPM to have different effects on prices and on service, which may increase or decrease due to RPM. A feature of the model which deviates from those found in the literature is due to the introduction of a class of consumers who do not search but decide on a purchase spontaneously. More interestingly social welfare is reduced by RPM (at least locally) exactly under those circumstances where RPM induces higher service (and price). Hence, welfare decreases exactly in the case which was frequently presented for the justification of RPM to promote service.
Keywords: L42; L13; D43; 330; resale price maintenance; service; welfare; Preisbindung; Buchhandel; Buch; Preis; Dienstleistung; Kundendienst; Wohlfahrtseffekt; Theorie